KESIAPAN CALON GURU SEKOLAH DASAR DALAM MENGHADAPI ERA REVOLUSI INDUSTRI - Kinanti Pangestu; Ni Luh Sakinah Nuraini (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
ABSTRACTThis research aims to analyze the readiness of prospective elementary school teachers who are students of the Elementary School Teacher Education (PGSD) study program of the State University of Malang in facing the era of the industrial revolution in terms of educational competence, competence for technological commercialization, competence in globalization, competence in the future strategies, and counselor competence. The research used a qualitative approach with a case study model. The results showed that the ability of prospective teachers in terms of these five aspects showed good results, namely from the aspect of educational competence. The results are quite good for the aspects of counselor competence. And the results are less for competence for technological commercialization, competence in globalization, and competence in future strategies. Keywords: readiness, prospective elementary school teachers, industrial revolution ABSTRAKPenelitian ini bertujuan untuk menganalisis kesiapan calon guru sekolah dasar siswa program studi Pendidikan Guru Sekolah Dasar (PGSD) Universitas Negeri Malang dalam menghadapi era revolusi industri ditinjau dari kompetensi pendidikan, kompetensi komersialisasi teknologi, kompetensi globalisasi, kompetensi strategi masa depan, dan kompetensi konselor. Penelitian menggunakan pendekatan kualitatif dengan model studi kasus. Hasil penelitian menunjukkan bahwa kemampuan calon guru ditinjau dari kelima aspek tersebut menunjukkan hasil yang baik yaitu dari aspek kompetensi pendidikan. Hasilnya cukup baik untuk aspek kompetensi konselor. Dan hasilnya kurang untuk kompetensi komersialisasi teknologi, kompetensi dalam globalisasi, dan kompetensi dalam strategi masa depan. Kata kunci: kesiapan, calon guru sekolah dasar, revolusi industri